2021
DOI: 10.1016/s2213-2600(21)00160-0
|View full text |Cite|
|
Sign up to set email alerts
|

Inhaled budesonide in the treatment of early COVID-19 (STOIC): a phase 2, open-label, randomised controlled trial

Abstract: Background Multiple early reports of patients admitted to hospital with COVID-19 showed that patients with chronic respiratory disease were significantly under-represented in these cohorts. We hypothesised that the widespread use of inhaled glucocorticoids among these patients was responsible for this finding, and tested if inhaled glucocorticoids would be an effective treatment for early COVID-19. Methods We performed an open-label, parallel-group, phase 2, randomised … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
260
1
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(294 citation statements)
references
References 30 publications
5
260
1
11
Order By: Relevance
“…Inhaled steroid, budesonide, has recently been shown to decrease respiratory symptoms. and possible progression to COVID-19 (6). Other studies have shown that inhaled steroids may decrease the ACE2 receptor, which may also be beneficial in decreasing SARS-CoV-2 binding (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhaled steroid, budesonide, has recently been shown to decrease respiratory symptoms. and possible progression to COVID-19 (6). Other studies have shown that inhaled steroids may decrease the ACE2 receptor, which may also be beneficial in decreasing SARS-CoV-2 binding (7).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone, a steroid, offers a significant benefit to decreasing inflammation with severe respiratory distress in COVID-19 (5). Inhaled steroids such as budesonide, are also showing a decrease in the respiratory symptoms with COVID-19 (6). Other studies have shown that inhaled steroids may decrease the ACE2 receptor, which may also be beneficial in decreasing the binding of SARS-CoV-2 virus (7).…”
Section: Introductionmentioning
confidence: 99%
“…The utility of corticosteroids emerged from the observation that patients with chronic respiratory disease, who make widespread use of inhaled glucocorticoids, were significantly underrepresented among those admitted to hospital with COVID-19 [135]. In a recent randomized controlled trial [136], the early administration (within seven days of the onset of mild symptoms) of inhaled budesonide, reduced the likelihood of needing urgent medical attention and reduced recovery time in adults after early COVID-19. An interesting observational matched-cohort study showed that early home treatment of 90 consecutive patients with mild COVID-19 by their family physicians according to a pathophysiologic and pharmacologic rationale almost completely prevented the need for hospital admission, due to progression toward more severe illness, compared to 90 age-, sex-, and comorbidities-matched patients who received other therapeutic treatments [67].…”
Section: Usefulness Of Anti-inflammatory Drugs Administered Upstream Of Hyperinflammationmentioning
confidence: 99%
“…Such explanation seems to be true also in asthmatic patients, controlled with inhaled corticosteroids (ICS), who display similar morbidity of infection of general population [36]. Indeed, budesonide (an ICS), largely employed in asthma, if administered at the initial phase of infection, has been recently shown to markedly reduce viral load and persistence, duration and severity of symptoms and timing of recovery in infected nonasthmatic patients [37]. Indeed, ICS are able to impair ACE2 expression on respiratory mucosa through the inhibition of type I IFN [38,39].…”
mentioning
confidence: 99%